8u+2-4(-3u+2)=4(u-1)

Simple and best practice solution for 8u+2-4(-3u+2)=4(u-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8u+2-4(-3u+2)=4(u-1) equation:


Simplifying
8u + 2 + -4(-3u + 2) = 4(u + -1)

Reorder the terms:
8u + 2 + -4(2 + -3u) = 4(u + -1)
8u + 2 + (2 * -4 + -3u * -4) = 4(u + -1)
8u + 2 + (-8 + 12u) = 4(u + -1)

Reorder the terms:
2 + -8 + 8u + 12u = 4(u + -1)

Combine like terms: 2 + -8 = -6
-6 + 8u + 12u = 4(u + -1)

Combine like terms: 8u + 12u = 20u
-6 + 20u = 4(u + -1)

Reorder the terms:
-6 + 20u = 4(-1 + u)
-6 + 20u = (-1 * 4 + u * 4)
-6 + 20u = (-4 + 4u)

Solving
-6 + 20u = -4 + 4u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-4u' to each side of the equation.
-6 + 20u + -4u = -4 + 4u + -4u

Combine like terms: 20u + -4u = 16u
-6 + 16u = -4 + 4u + -4u

Combine like terms: 4u + -4u = 0
-6 + 16u = -4 + 0
-6 + 16u = -4

Add '6' to each side of the equation.
-6 + 6 + 16u = -4 + 6

Combine like terms: -6 + 6 = 0
0 + 16u = -4 + 6
16u = -4 + 6

Combine like terms: -4 + 6 = 2
16u = 2

Divide each side by '16'.
u = 0.125

Simplifying
u = 0.125

See similar equations:

| 9z+4-8=27 | | M+8=2m+1 | | -2(4s-5)-10=-2(6s+2)-2 | | 2x(x-3)=1+4x | | t^2-6t-4=0 | | F(-3)=9x-5 | | 12X^2-48X+34=0 | | 9y+2x(5y-19)=38 | | .45x+.05(14-x)=.10(79) | | X+.4444=.75 | | 7x+12y=240 | | 1.5*e=6 | | 9y+2x(5x-19)=38 | | 5x-2(3x+5)=10x+32 | | 3p+5=-7+5p | | 5x-3y+12w+2y-4w+7x= | | 2(x-3)-9=6x-4(5+x) | | s+4-2i=0 | | X^2+y^2+4x-14y+4=0 | | 9y+2x(5-19)=38 | | 10+3k=4(8-6k)+5 | | -110=-7(-6m-4)+4m | | 7x-2=a | | 64=16*d | | x=0.6x+984 | | 2(f-6)=8 | | 384+0.6x= | | 12ab-4b=0 | | -10y+18=-(5y-7)+5y | | 23x=45 | | -2x+4+7=29 | | 3x-2x+20=4x-20 |

Equations solver categories